2021
DOI: 10.31234/osf.io/xp6kh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seizing the Opportunity: Lifespan Differences in the Effects of the Opportunity Cost of Time on Cognitive Control

Abstract: Previous work suggests that lifespan developmental differences in cognitive control reflect maturational and aging-related changes in prefrontal cortex functioning. However, complementary explanations exist: It could be that children and older adults differ from younger adults in how they balance the effort of engaging in control against its potential benefits. Here we test whether the degree of cognitive effort expenditure depends on the opportunity cost of time (average reward rate per unit time): if the ave… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While this assumption was reasonable given the parameters of our task (i.e., where incentives were explicitly cued and pseudorandomized), a crucial next step will be to examine how people dynamically reconfigure control as they learn from feedback that the expected rewards and penalties in their environment are changing. Research has shown that people dynamically adjust their response threshold in both decision-making tasks [56] and cognitive control tasks [30,57] as they learn to expect greater rewards. It remains to be tested how these cognitive control adjustments are distributed across both threshold and drift rate with changes in both reward and punishment, as well as with individualspecific [58,59] and context-specific [60] differences in learning from these positive and negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While this assumption was reasonable given the parameters of our task (i.e., where incentives were explicitly cued and pseudorandomized), a crucial next step will be to examine how people dynamically reconfigure control as they learn from feedback that the expected rewards and penalties in their environment are changing. Research has shown that people dynamically adjust their response threshold in both decision-making tasks [56] and cognitive control tasks [30,57] as they learn to expect greater rewards. It remains to be tested how these cognitive control adjustments are distributed across both threshold and drift rate with changes in both reward and punishment, as well as with individualspecific [58,59] and context-specific [60] differences in learning from these positive and negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found social cognition to be more effortful for preadolescent children and more reliant on executive functioning and general reasoning skills compared to adolescent and adult samples ( Devine & Hughes, 2013;Dumontheil, Apperly, & Blakemore, 2010). One study, specifically, found that children's social and reward decisions relied on more cognitive resources, compared to those of older age groups (Devine et al, 2021). This may be due to a critical stage in brain reorganization supporting cognitive skills in both TD and autistic preadolescent children.…”
Section: Neuro-developmental Changes In Preadolescence and Their Effe...mentioning
confidence: 98%